The role of complementary monetary system as an instrument to innovate the local financial system - Alexandra Lenis Escobar; Ramón Rueda López; Miguel Ángel Solano-Sánchez; María de los Ba\~nos García-Moreno García (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
For decades, complementary monetary systems (CMSs) and open innovation in the local area have coexisted alongside official currencies. Today, when it is most necessary to innovate and act locally to solve global problems, it is appropriate to increase the usefulness of financial instruments, such as social and complementary currencies, which can contribute to building more sustainable and resilient cities and thus achieve the Sustainable Development Goals (SDGs). This research, through a synthetic analysis, contributes to the scientific debate on the usefulness of the CMSs. It examines the practical way in which these instruments can be used to innovate in local financial systems as elements capable of promoting and dynamizing the economic and social relations of a locality.
Keywords: 650; innovation; cities; complementary monetary systems; local area; SDG; sustainable local development; urban resilience